The Measurement of Income Distribution Dynamics when Demographics are correlated with Income - Michael Grimm; Denis Cogneau (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2005)
The purpose of our paper is to derive instructive analytics on how to account for differentials in demographic variables, in particular mortality, when performing welfare comparisons over time. The idea is to apply various ways of 'correcting' estimated income distribution measures for 'sample selection' due to differential mortality. We implement our approach empirically using three waves of the Indonesian Family Life Surveys (IFLS). We distinguish the direct effect of mortality, i.e. individuals who die leave the population and no longer contribute to monetary welfare, from the indirect effect, i.e. the impact on survivors in the deceased's household who may experience a decrease or increase in monetary welfare. In the case of Indonesia, we show that the direct and indirect effects of mortality on income distribution have opposite signs, but are roughly the same in magnitude. We also show that the effects of other demographic changes - such as changes in the structure of fertility, migration and educational attainment - dominate the effects of mortality, whether direct or indirect. However, we find that none of these demographic developments is substantial enough to explain a significant part of the change in income distribution, regardless of whether the pre-crisis period (1993-1997) or the post-crisis period (1997-2000) is considered.
Keywords: D10; D63; J17; 330; Differential Mortality; Income Distribution Dynamics; Welfare Comparisons; Decomposition; Einkommensverteilung; Sterblichkeit; Soziale Mobilität; Sozialer Indikator; Wohlfahrtseffekt; Schätzung; Indonesien